PENILAIAN STATUS GIZI PADA BALITA SEBAGAI BENTUK PENCEGAHAN STUNTING DAN PELAYANAN KHITAN GRATIS DI KOTA JAMBI - Ridwan Ridwan; Aulia Satria; Armaidi Darmawan; Nuriyah; Imat Rahmatulillah (Universitas Jambi, 2023)
ABSTRACT Introduction: Nutritional status in Indonesia in 2022 shows that 24.4% of children are stunted. Stunting is not only a problem in Indonesia but also in the world. In Jambi province, the prevalence of stunting is 22.4% (SSGI 2021) where the highest category is based on WHO, at least 20%. Circumcision or circumcision is an operative procedure with the aim of preventing the accumulation of smegma which can cause inflammation. This activity was followed by 35 toddlers who carried out nutritional status checks where 16 toddlers were detected stunting while the circumcision service was attended by 16 participants where the youngest participant was 4 years old and the oldest was 11 years old. Method: This activity was carried out on October 20, 2022 in Jambi City. Previously the participants would be recorded first. To assess the nutritional status of participants, measurements of height, weight and a brief history with their mothers will be carried out. While circumcision services are carried out or carried out by a medical and paramedical team according to their expertise. Results: From this activity, it was found that the Nutritional Status of the children examined was 16 people (45.715%) suffering from stunting, and 18 people (51.43%) with severe stunting. Meanwhile, based on nutritional status, 18 children (51.43%) were underweight and 9 children (25.71) were severely underweight. Conclusion: From this activity it was concluded that there are still many children who suffer from stunting and underweight in the city of Jambi so that better management is needed by the government and the community. Keyword: Nutritional Status, circumcision ABSTRAK Pendahuluan: Status gizi di Indonesia pada tahun 2022 didapatkan 24,4% anak mengalami stunting. Stunting bukan hanya permasalahan di Indonesia saja tetapi juga didunia. Di provinsi jambi sendiri prevalensi stunting sebesar 22,4% (SSGI 2021) dimana kategori tertinggi berdasarkan WHO minimal 20%. Khitan atau sirkumsisi merupakan suatau tindakan operatif dengan tujuan mencegah terjadinya penumpuka smegma yang dapat menyebabkan inflamasi. Dari kegiatan ini diikuti 35 balita yang melakukan pemeriksaan status gizi dimana 16 balita terdeteksi stunting sedangkan pada pelayanan khitan diikuti 16 peserta dimana peserta yang termuda berusi 4 tahun dan tertua berusia 11 tahun. Metode: Kegiatan ini dilaksanakan pada tanggal 20 Oktober 2022 di Kota Jambi. Sebelumnya peserta akan didata terlebih dahulu. Untuk penilaian status gizi peserta akan dilakukan pengukuran tinggi badan, berat badan serta anamesis secara singkat dengan ibunya. Sedangkan pelayanan khitan dilakukan atau dikerjakan oleh tim medis dan paramedis sesuai dengan keahliannya. Hasil: Dari kegiatan ini didapatkan Status Gizi TB/U anak yang diperiksa, yang menderita stunting sebanyak 16 orang (45,715%), dan severe stunting sebanyak 18 orang (51,43%). Sedangkan berdasarkan status gizi BB/U didapatkan anak yang underweight sebanyak 18 orang (51,43%) dan severe underweight sebanyak 9 orang (25,71). Kesimpulan: Dari kegiatan ini disimpulkan bahwa masih banyaknya anak yang menderita stunting dan underweight di Kota Jambi sehingga diperlukan penanggulangan yang lebih baik lagi oleh pemerintah maupun masyarakat. Kata Kunci: Status Gizi, Sirkumsisi